Investigation of Incidence and Risk Factors for Surgical Glove Perforation in Small Animal Surgery. Issue 4 (11th March 2014) - Hayes, Galina M.; Reynolds, Deborah; Moens, Noel M.M.; Singh, Ameet; Oblak, Michelle; Gibson, Thomas W.G.; Brisson, Brigitte A.; Nazarali, Alim; Dewey, Cate
<x xml:space="preserve">Abstract</x> Objective To identify incidence and risk factors for surgical glove perforation in small animal surgery. Study Design Observational cohort study. Sample Population Surgical gloves (n = 2132) worn in 363 surgical procedures. Methods All gloves worn by operative personnel were assessed for perforation at end‐procedure using a water leak test. Putative risk factors were recorded by a surgical team member. Associations between risk factors and perforation were assessed using multivariable multi‐level random‐effects logistic regression models to control for hierarchical data structure. Results At least 1 glove perforation occurred in 26.2% of procedures. Identified risk factors for glove perforation included increased surgical duration (surgery >1 hour OR = 1.79, 95% CI = 1.12–2.86), performing orthopedic procedures (OR = 1.88; 95% CI = 1.23–2.88), any procedure using powered instruments (OR = 1.93; 95% CI = 1.21–3.09) or surgical wire (OR = 3.02; 95% CI = 1.50–6.05), use of polyisoprene as a glove material (OR = 1.59, 95% CI = 1.05–2.39), and operative role as primary surgeon (OR = 2.01; 95% CI = 1.35–2.98). The ability of the wearer to detect perforations intraoperatively was poor, with a sensitivity of 30.8%. Conclusions There is a high incidence of unrecognized glove perforations in small animal surgery.